Aligned and Graded Type‐II Ruddlesden–Popper Perovskite Films for Efficient Solar Cells. Issue 21 (8th May 2018) - Qing, Jian; Liu, Xiao‐Ke; Li, Mingjie; Liu, Feng; Yuan, Zhongcheng; Tiukalova, Elizaveta; Yan, Zhibo; Duchamp, Martial; Chen, Shi; Wang, Yuming; Bai, Sai; Liu, Jun‐Ming; et al.
Abstract: Recently, Ruddlesden–Popper perovskites (RPPs) have attracted increasing interests due to their promising stability. However, the efficiency of solar cells based on RPPs is much lower than that based on 3D perovskites, mainly attributed to their poor charge transport. Herein, a simple yet universal method for controlling the quality of RPP films by a synergistic effect of two additives in the precursor solution is presented. RPP films achieved by this method show (a) high quality with uniform morphology, enhanced crystallinity, and reduced density of sub‐bandgap states, (b) vertically oriented perovskite frameworks that facilitate efficient charge transport, and (c) type‐II band alignment that favors self‐driven charge separation. Consequently, a hysteresis‐free RPP solar cell with a power conversion efficiency exceeding 12%, which is much higher than that of the control device (1.5%), is achieved. The findings will spur new developments in the fabrication of high‐quality, aligned, and graded RPP films essential for realizing efficient and stable perovskite solar cells. Abstract : A simple and universal method involving the use of two synergistic additives (dimethylsulfoxide and methylammonium chloride) into precursor solution is reported for growing high‐quality Ruddlesden–Popper perovskite films. Based on this method, hysteresis‐free solar cells with power conversion efficiencies over 12% and excellent reproducibility are achieved.